Immunotherapies of retinoblastoma: Effective methods for preserving vision in the future - Wang, Ling; Li, Shixu; Mei, Jun; Ye, Lin (Frontiers in Oncology, 2022)
Retinoblastoma is the most common intraocular tumor in children. Patients can be cured by enucleation, but it can lead to vision loss. Chemotherapy is the main method of treatment for RB currently. Unfortunately, chemoresistant and tumor metastasis often happen, that resulting in relatively poor prognosis. Therefore, immunotherapy becomes one of the optimal choices. Targeting not only tumor cells but also the active tumor microenvironment is a novel strategy for RB treatment. Here, we conclude several potential targets for RB immunotherapy, including gangliosides GD2, PD-1 and PD-L1, B7H3, EpCAM and SYK. We also review the techniques for CART, bispecific antibody and genetically modified Dendritic cells acording to the characteristics of different targets and discuss the fasibility of immunotherapy with different targets.